2017
DOI: 10.5705/ss.202015.0019
|View full text |Cite
|
Sign up to set email alerts
|

A general construction for space-filling Latin hypercubes

Abstract: We propose a general method for constructing Latin hypercubes of flexible run sizes for computer experiments. The method makes use of arrays with a special structure and Latin hypercubes. By using different such arrays and Latin hypercubes, the proposed method produces various types of Latin hypercubes including orthogonal and nearly orthogonal Latin hypercubes, sliced Latin hypercubes, and Latin hypercubes in marginally coupled designs. In addition, the proposed algebraic design construction is particularly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To better illustrate the performance of these three methods, we define the Moreover, Lin and Kang (2016)'s method can also be used for generating maximin LHDs under the φ r criterion. Their numerical results have showed that the designs constructed by Lin and Kang (2016)'s method have larger φ r values (so worse) than the designs constructed by the R package SLHD; while our designs have smaller φ r value than designs constructed by the R package SLHD, so our designs perform better than the designs obtained by Lin and Kang (2016)'s method. As an example, using N = 404, we obtain an LHD(100, 50).…”
Section: Theoretical Results and Comparisonsmentioning
confidence: 78%
See 2 more Smart Citations
“…To better illustrate the performance of these three methods, we define the Moreover, Lin and Kang (2016)'s method can also be used for generating maximin LHDs under the φ r criterion. Their numerical results have showed that the designs constructed by Lin and Kang (2016)'s method have larger φ r values (so worse) than the designs constructed by the R package SLHD; while our designs have smaller φ r value than designs constructed by the R package SLHD, so our designs perform better than the designs obtained by Lin and Kang (2016)'s method. As an example, using N = 404, we obtain an LHD(100, 50).…”
Section: Theoretical Results and Comparisonsmentioning
confidence: 78%
“…As an example, using N = 404, we obtain an LHD(100, 50). By deleting the last two columns and the last two rows, and rearranging the levels for each column, we obtain an LHD(98, 48) with a φ r value of 0.1096, which is better than any of the LHD(98, 48)'s constructed by Lin and Kang (2016)'s method (whose smallest φ r value is 0.1164). The φ r values are evaluated on standardized designs with n levels scaled to [0.5/n, 1 − 0.5/n].…”
Section: Theoretical Results and Comparisonsmentioning
confidence: 98%
See 1 more Smart Citation
“…Criteria based on orthogonality, distance and discrepancy can all be used for this purpose. Some related recent work includes Georgiou & Efthimiou (), Liu & Liu (), Lin & Kang (), and Xiao & Xu ().…”
Section: Discussionmentioning
confidence: 99%
“…An intuitive approach for constructing space‐filling designs is to employ an algorithmic search or a construction method based on a distance or discrepancy criterion; see Johnson, Moore & Ylvisaker (1990) and Fang, Li & Sudijanto (2006) for early work, and Moon, Dean & Santner (2011), Lin & Kang (2016), Wang, Xiao & Xu (2018), and Sun, Wang & Xu (2019) for more recent developments. Inspired by false(t,m,sfalse)‐nets from quasi‐Monte Carlo methods (Niederreiter, 1992), He & Tang (2013) introduced and studied strong orthogonal arrays (SOAs).…”
Section: Introductionmentioning
confidence: 99%